Intron length polymorphism of β-tubulin genes in Deschampsia antarctica É. Desv. across the western coast of the Antarctic Peninsula - Rabokon, A.M.; Pirko, Y.V.; Demkovych, A. Ye; Andreev, I.O.; Parnikoza, I.Yu.; Kozeretska, I.A.; Yu, Z.; Kunakh, V.A.; Blume, Y.B. (Polar Science, 2019)
The origin of one from two native vascular plants in Antarctic, the Antarctic hairgrass (Deschampsia antarctic É. Desv.) (Poaceae), remains unclear. Molecular genetic analyses have demonstrated low genetic heterogeneity among representatives of this species. The search for new marker nucleotide sequences of the Antarctic hairgrass is justified, which would be useful in clarifying the phylogeographic origin, heterogeneity and population dynamics of D. antarctica. Here we report the results of a comparative analysis of the introns of β-tubulin genes for several populations of the Antarctic hairgrass across the maritime Antarctic. We demonstrate that the first intron of the β-tubulin gene contain markers capable of discriminating D. antarctica subpopulations in the maritime Antarctic. The sequence of the first intron of the β-tubulin gene can therefore be used for more detailed population genetics studies of D. antarctica. journal article